ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI UNDERPRICING SAHAM PADA PENAWARAN UMUM PERDANA - Rahma, Anneu Cania; Wiharno, Herma; Nurhandika, Arief (Program Studi Akuntansi, Universitas Kuningan, 2024)
This study aims to examine and analyze what factors influence stock underpricing in companies that carry out Initial Public Offerings. The research method used in this research is descriptive method and verification method. The population in this study are all companies that are conducting Initial Public Offerings in 2019-2021. The samples obtained using quota sampling are 145 companies. The analysis technique used is multiple linear regression. Data processing uses the IBM SPSS 20 program The results of this study indicate that profitability, market value, liquidity, and firm age has a negative and significant effect on stock underpricing. Capital structure has a positive and significant effect on stock underpricing. All variables in this study have significant influence on stock underpricing. Then the regression estimation results show that the predictive ability of the 5 independent variables on stock underpricing is 73%, while the remaining 27% is influenced by other factors outside the model which are not included in this analysis. Keywords: Profitability, Market Value, Capital Structure, Liquidity, Firm Age, Underpricing.